Preparation of antibacterial acrylic bone cement with methacrylate derived from benzothiazole. (May 2021) - Zhu, Wenbin; Liu, Fang; Yu, Biao; He, Jingwei
Abstract: Methacrylate derived from benzothiazole (BTTMA) was incorporated into acrylic bone cement with a series of mass ratio (5 wt%, 10 wt%, and 15 wt%) with the aim to endow antibacterial activity. Properties such as dough time (tdough ), setting time (tset ), maximum temperature (Tpeak ), fluid uptake, water solubility, mechanical properties, and biocompatibility of BTTMA containing bone cements were all investigated. Bone cement without BTTMA was used as control and named as plain cement. The results showed that, after incorporating BTTMA, tdough, flexural modulus, compressive strength of bone cements could be increased, while tset, Tpeak, fluid uptake, water solubility, and flexural strength would be reduced. All of BTTMA containing bone cements did not show hemolytic activity and cell toxicity, but only bone cement with 15 wt% of BTTMA showed antibacterial activity against Staphylococcus aureus ( S. aureus ).